Readiness Measurement of Integrated Stunting Prevention System Users (SIMPATI) Using Technology Readiness Index (TRI) - Siti Nida, Siti Nida Saripah (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2024)
SIMPATI (Integrated Stunting Prevention System) is one of the Sumedang Digital Region programs in collaboration with the Sumedang Regency Government and Telkomsel to accelerate the handling of child development disorders or stunting. In 2018, the stunting rate in Sumedang Regency reached 32%. However, after implementing SIMPATI, the stunting prevalence rate in Sumedang district has decreased in the last five years, from 32.2% in 2018, to 8.27% in 2022. Seeing this success, the Minister of Health of the Republic of Indonesia (Menkes) Budi Gunadi Sadikin stated "the sympathy application will be tested for use in 50 districts and cities". Before being tested by other cities, it is necessary to evaluate the system using the Technology Readiness Index (TRI) method with the aim of knowing the level of readiness of SIMPATI users, so that in the future the developer can update it as needed. To measure user readiness, this method uses four variables, namely optimism, innovativeness, discomfort, and insecurity. Respondents to this study consisted of cadres/Puskesmas, Executives/Government and the general public/Parents with a TRI score of 0.335 which is categorized in the medium technology readiness index, thus users of the SIMPATI application in Sumedang city are ready to use the SIMPATI application taking into account the aspects of discomfort and insecurity that are still get low scores of 0.786 and 1.13.